Regeneration of Cochlear Efferent Nerve Terminals after Gentamycin Damage - Hennig, Anne K. (J Neurosci, 1998)
Chickens recover auditory function after hair cell loss caused by ototoxic drug damage or acoustic overstimulation, indicating that mechanisms exist to reestablish appropriate neuronal connections to regenerated hair cells. However, despite similar hair cell regeneration times, hearing recovery takes substantially longer after aminoglycoside than after sound damage. We have therefore begun examining damage and regeneration of efferent nerve terminals by immunolabeling whole-mount cochleae for differentially localized synaptic proteins and by visualizing the distribution of label with confocal microscopy. In undamaged cochleae, the synaptic proteins synapsin and syntaxin show similar distribution patterns corresponding to the large cup-like terminals on short hair cells. After gentamycin administration, these terminals are disrupted as hair cells are lost, leaving smaller, more numerous synapsin-reactive structures in the sensory epithelium. Syntaxin reactivity remains associated with the extruded hair cells, indicating that the presynaptic membrane is still attached to the postsynaptic site. In contrast, after sound damage, both synapsin and syntaxin reactivity are lost from the epithelium with extruded hair cells. As regenerated hair cells differentiate after gentamycin treatment, the synapsin labeling associated with cup-like efferent endings reappears but is not completely restored even after 60 d of recovery. Thus, efferent terminals are reestablished much more slowly than after sound damage (Wang and Raphael, 1996), consistent with the prolonged loss of hearing function. This in vivo model system allows comparison of axonal reconnection after either complete loss (sound damage) or partial disruption (gentamycin treatment) of axon terminals. Elucidating the differences in recovery between these injuries can provide insights into reinnervation mechanisms.